2021
DOI: 10.1136/jnnp-2020-324349
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in frontotemporal lobar degeneration syndromes

Abstract: After decades of research, large-scale clinical trials in patients diagnosed with frontotemporal lobar degeneration (FTLD) are now underway across multiple centres worldwide. As such, refining the determinants of survival in FTLD represents a timely and important challenge. Specifically, disease outcome measures need greater clarity of definition to enable accurate tracking of therapeutic interventions in both clinical and research settings. Multiple factors potentially determine survival, including the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 95 publications
1
6
0
1
Order By: Relevance
“…As to the median survival of PPA-MND patients – i.e., ≈3 years –, it was slightly lower than that of patients with PPA only ( Montembeault et al, 2018 ), this agreeing with the fact that MN involvement represents a risk factor for a shorter survival in PPA patients ( De La Sablonnière et al, 2021 ; El-Wahsh et al, 2021 ). Its high heterogeneity herewith found might be accounted for by the diversities across both PPA and MND phenotypes – since survival is longer in SD than in PNFA ( Tastevin et al, 2021 ), and shorter in classical ALS as compared to atypical MND variants – such as predominant-UMN phenotypes ( Turner and Talbot, 2020 ), which were relatively highly represented (25.5%) among PPA-MND patients.…”
Section: Discussionsupporting
confidence: 67%
“…As to the median survival of PPA-MND patients – i.e., ≈3 years –, it was slightly lower than that of patients with PPA only ( Montembeault et al, 2018 ), this agreeing with the fact that MN involvement represents a risk factor for a shorter survival in PPA patients ( De La Sablonnière et al, 2021 ; El-Wahsh et al, 2021 ). Its high heterogeneity herewith found might be accounted for by the diversities across both PPA and MND phenotypes – since survival is longer in SD than in PNFA ( Tastevin et al, 2021 ), and shorter in classical ALS as compared to atypical MND variants – such as predominant-UMN phenotypes ( Turner and Talbot, 2020 ), which were relatively highly represented (25.5%) among PPA-MND patients.…”
Section: Discussionsupporting
confidence: 67%
“…One of the important results of our study is that despite the relatively benign early presentation, a high proportion of nfvPPA cases developed motor disturbances such as MND, PSP, and CBS and it is conceivable that these syndromes increase mortality risk. Although, only 12 patients deceased in the follow-up and a larger sample size longitudinal study has reported a longer survival in nfvPPA [ 44 ], and a large body of literature has showed a significant shorter survival in FTD patients with motor disturbances [ 45 , 46 ]. The relationship between pyramidal, extrapyramidal symptoms, and nfvPPA have been reported previously [ 11 , 47 50 ], and some authors have suggested that apraxia of speech is the clinical marker of progression to PSP and CBS [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS; also known as motor neuron disease) is a related neurodegenerative disease characterized by loss of motor neurons leading to physical motor impairment [5][6][7] . bvFTD and ALS exist on a disease spectrum with the majority of cases having the same causal pathogenic protein, trans-activation response (TAR) DNAbinding protein , encoded by TARDBP [8][9][10] . TDP-43 is a DNA/RNA-binding protein that regulates a number of transcriptional and translational processes 11 .…”
mentioning
confidence: 99%